Selected Issues Concerning the Translation of Emotional Predicates in the Slovene Version of Henryk Sienkiewicz’s Without Dogma - Zatorska, Agnieszka (Slavic Languages Today: Categories, Structures and Processes, 2021)
This article is devoted to a set of verbs and analytical constructions expressing emotional predicates. The lexical units discussed in the paper have been extracted from the original Polish version of the novel Bez dogmatu (English translation: Without Dogma) by Henryk Sienkiewicz and the Slovene translated version. The aim of the study is to present an inventory of the lexemes under consideration in the Polish source text and to discuss their equivalents in the Slovene target text. Firstly, a verb used in the source text can be translated by a verb of the target language as well as by an analytical construction. Secondly, one Polish lexeme is sometimes rendered using a few Slovene equivalents, e.g. Polish bać się – Slovene bati se, zbati se, upati si, ustrašiti se, biti komu strah. Thirdly, an analytical construction can be translated by another analytical construction as well as a verb. The discussion focuses on modifications of analytical constructions, particularly those of the verbo-nominal type. Metaphorical units (such as Bojaźń chwyta, Gniew porywa, Trwoga zamieszkała) are presented as a separate group. The analysis confirms similarities and differences between the source and the target texts in terms of the use of the lexical units under discussion. The differences identified in the study are classified according to the type of transformation they involve in translation.